FILM INDUCED TOURISM AS A MECHANISM FOR TERRITORIAL DEVELOPMENT? - Enrico Nicosia (Bollettino della Società Geografica Italiana, 2019)
This paper addresses the correlation between the power of movies and television series as a motivational and imagemaking tool and the attractiveness of tourism destinations. In light of this relationship, the research analyses the phenomenon of film-induced tourism in the Marche Region. This phenomenon has been recognized and reported, but very few comprehensive studies of it have been published. The evidence that has been put forward to date has been mostly anecdotal, pointing towards the capacity of popular films and television series to attract tourists, in the form of enthusiastic fans. Despite the fact that statistics directly concerning the impact that films have had on tourism are limited, there are some countries such as the United Kingdom have an increasing interest in studying and developing film-induced tourism. As for the Marche Region, unfortunately, as far as can be seen from the survey conducted, high knowledge of the phenomenon under study is not apparent in the sample of interviewees.